Environmental health policies in Europe: successes and failures in Switzerland, Germany and Belgium. (2015) - Forbat, Julien
While European countries insist on the necessity to develop environmental health policies, mainly at the international level, a careful analysis of national policy processes, focused on national environmental health action plans (NEHAPs) and national strategies of sustainable development (NSSDs), tends to show that results obtained are particularly limited. This study investigates the reasons for this surprising 'environmental health paradox'. Data used in this study have been obtained from interviews conducted among experts of the Swiss, German and Belgian environmental health policies and from survey results provided by the WHO Regional Office for Europe in Bonn (WHO/Europe). Findings show that major obstacles to more ambitious environmental health policies arise from their lack of political recognition at the national level, from their confinement to measures of scientific research and from the absence of any substantial system of indicators capable of correctly assessing environmental health issues and policy outcomes.